Deformation understanding in the Upper Paleozoic of Ventana Ranges at Southwest Gondwana Boundary - Arzadún, Guadalupe (2021)
At the east of the Ventana Ranges, Buenos Aires, Argentina, outcrops the Carboniferous-Permian Pillahuincó Group (Sauce Grande, Piedra Azul, Bonete and Tunas Formation). We carried out an Anisotropy of Magnetic Susceptibility (AMS) study on Sauce Grande, Piedra Azul and Bonete Formation that displays ellipsoids with constant Kmax axes trending NW–SE, parallel to the fold axes. The Kmin axes are orientated in the NE–SW quadrants, oscillating from horizontal (base of the sequence-western) to vertical (top of the sequence-eastern) positions, showing a change from tectonic to almost sedimentary fabric. This is in concordance with the type and direction of foliation measured in petrographic thin sections which is continuous and penetrative to the base and spaced and less developed to the top. We integrated this study with previous Tunas Formation results (Permian). Similar changes in the AMS pattern (tectonic to sedimentary fabric), as well as other characteristics such as the paleo-environmental and sharp curvature in the apparent polar wander path of Gondwana, marks a new threshold in the evolution of the basin. Those changes along the Pillahuincó deposition indicate two different spasm in the tectonic deformation that according to the ages of the rocks are 300–290 Ma (Sauce Grande to Bonete Formation deposition) and 290–276 Ma (Tunas Formation deposition). This Carboniferous-Permian deformation is locally assigned to the San Rafael (Hercinian) orogenic phase, interpreted as the result of rearrangements of the microplates that collided previously with Gondwana, and latitudinal movements of Gondwana toward north and Laurentia toward south to reach the Triassic Pangea.